Secondary Students’ Perceptions of Teaching Quality and Teacher-Family Interaction: A Structural Equation Model - Hong, Meiyang; Brown, Gavin T. L. (New Zealand journal of educational studies, 2024)
Students’ perceptions of teaching quality and teachers’ interaction with their families, along with student self-efficacy and interest in a subject matter to performance. However, little is known about how student perceptions of teaching quality and teacher-family interactions in the subject of English relate to performance in reading comprehension. The current study explores how the teacher-related perceptions of New Zealand senior secondary students relate to their reading attitudes and tested reading comprehension. Partially mediated structural equation modelling revealed that students’ perceptions of teaching quality directly and positively influenced student self-efficacy, interest, and performance and indirectly through self-efficacy. However, perceptions of teacher-family interactions negatively influenced student self-efficacy and performance and were not related to interest. Although the model was statistically invariant across demographic variables, there were large latent mean differences across school decile bands for reading performance. These findings reinforce the importance of student perceptions of good teaching and raise challenges about how teachers interact with families.